Differential Attention Functioning in Pediatric Chronic Kidney Disease - Duquette, Peter J.; Gipson, Debbie S.; Hooper, Stephen R. (Frontiers in Human Neuroscience, 2022)
Objective To compare specific attention functions for school-age children with chronic kidney disease (CKD) to those of a typically developing control group. Methods A cross-sectional study examined attention dimensions for children and adolescents with CKD (n = 30) in comparison to a typically developing control group (n = 41). The CKD group consisted of those receiving maintenance dialysis (n = 15) and those with mild/moderate CKD treated conservatively (n = 15). Measures aligning with Mirsky’s conceptual multidimensional model of attention were selected to compare groups across five dimensions of attention: Focus/Execute, Sustain, Stability, Shift, and Encode. Results Significant group differences were revealed, with the CKD group performing worse than controls on the Focus/Execute, Sustain, and Encode dimensions. The CKD group also had a larger proportion of children with scores one standard deviation or more below the mean on the Shift and Encode domains, suggesting an at-risk level of functioning in these dimensions. Secondary analyses showed disease severity to be correlated with worse attention functions for children with CKD. Conclusion Children with CKD may be vulnerable to subtle, specific deficits in numerous attention dimensions relative to their typically developing peers, particularly for those with more severe disease.